From Slaves of Sin to Slaves of God: Reconsidering the Origin of Paul's Slavery Metaphor in Romans 6 - Goodrich, John K. 1981- (2013)
The origin of Paul's δοῦλος metaphors has long captured the attention of NT interpreters. While many scholars maintain that these images were principally influenced by one of the modes of physical slavery practiced in the Greco-Roman world, others propose that the metaphors derive exclusively from the servant/slave of God motif enlisted throughout Jewish literature. Concentrating on Romans 6, this article provides a detailed survey of three recent contributions to the Jewish-only position (those by Richard Horsley, John Byron, and Tom Holland, respectively) before responding critically to them at three points. The article ultimately seeks to assert that Paul's δοῦλος metaphor in Romans 6 (and elsewhere), while functioning as an extension of a Jewish theological motif, was significantly influenced by Greco-Roman notions of domestic slavery.